THE ROLE OF GERMANY'S MIGRATION POLICY IN SECURING THE NATIONAL INTERESTS OF THE REPUBLIC OF UZBEKISTAN (Scientific electronic journal "Labor Economics and Human Capital", 2026)
This article analyzes the impact of the Federal Republic of Germany's migration policy on the practical implementation of the national interests of the Republic of Uzbekistan. Through a comprehensive analysis of bilateral agreements, official documents, and published expert assessments, the study examines the challenges and opportunities that arise from the migration partnership between the two countries. Particular attention is given to the 2025 Agreement on a Comprehensive Partnership in Migration and Mobility. The article considers the significance of this agreement for economic development and demographic policy, as well as for Uzbekistan's positioning on the international stage.
Keywords: migration policy, national interests, Germany, Uzbekistan, labor migration, skilled professionals, bilateral cooperation.